Essential oils in the control of Botrytis cinera: Influence on post harvest quality of Rubi grapes - Garcia, Carla; Rodrigues, João Domingos [UNESP]; Mazaro, Sergio Miguel; Botelho, Renato Vasconcelos; Faria, Cacilda Márcia Duarte Rios (FapUNIFESP (SciELO), 2019)
Agrochemicals are used to control diseases in post-harvest grapes, but although efficient, they may cause human health problems. Thus, the objective of the present work was to verify the potential of the volatile compounds present in the essential oils of the fruits pitanga (EOP), guaçatonga (EOG) and melaleuca (EOM) in the control of Botrytis cinerea both in vitro and inoculated in ' Rubi ' grapes, as well as to verify the induction of resistance in these fruits. Thus, B. cinerea mycelial growth, grey mould control in 'Rubi' grapes, post-harvest quality of the grapes and the activities of the enzymes polyphenoloxidase (PPO), phenylalanine ammonium lyase (PAL), glucanase (GLU) and chitinase, were evaluated. According to the results it was observed that the volatile compounds released by the essential oils reduced the rates of mycelial growth of B. cinerea and of the grey mould disease, and the treatments with the volatiles from EOP and EOG activated the resistance induction mechanisms of these fruits. Thus, EOP and OEG release compounds that can act directly on B. cinerea and also induce resistance in the 'Rubi' grapes, reducing the grey mould in these grapes.
Óleos essenciais no controle de Botrytis cinerea: Influência na qualidade pós-colheita de uvas 'Rubi'
Keywords: Chitinase; Glucanase; Phenylalanine ammonia lyase; Polyphenoloxidase